Genome-Wide Analysis of the DREB Subfamily in Saccharum spontaneum Reveals Their Functional Divergence During Cold and Drought Stresses - Huang, Xing; Song, Xiupeng; Chen, Rongfa; Zhang, Baoqing; Li, Changning; Liang, Yongsheng; Qiu, Lihang; Fan, Yegeng; Zhou, Zhongfeng; Zhou, Huiwen; Lakshmanan, Prakash; Li, Yangrui; et al. (Frontiers in Genetics, 2020)
Drought and cold stresses are the main environmental factors that affect the yield of sugarcane, and DREB genes play very important roles in tolerance to drought, cold, and other environmental stresses. In this study, bioinformatics analysis was performed to characterize Saccharum spontaneum SsDREB genes. RNA-seq was used to detect the expression profiles of SsDREBs induced by cold and drought stresses. According to our results, there are 110 SsDREB subfamily proteins in S. spontaneum, which can be classified into 6 groups; 106 of these genes are distributed among 29 chromosomes. Inter- and intraspecies synteny analyses suggested that all DREB groups have undergone gene duplication, highlighting the polyploid events that played an important role in the expansion of the DREB subfamily. Furthermore, RNA-seq results showed that 45 SsDREBs were up- or downregulated under cold stress; 35 of them were found to be involved in responding to drought stress. According to protein-protein interaction analysis, SsDREB100, SsDREB102 and SsDREB105 play key roles during the response to cold stress. These results reveal that functional divergence exists between collinear homologous genes or among common origin genes in the DREB subfamily of S. spontaneum. This study presents a comprehensive analysis and systematic understanding of the precise mechanism of SsDREBs in response to abiotic stress and will lead to improvements in sugarcane.